Immigration Reform: The Effects of Employer Sanctions and Legalization on Wages - Cobb-Clark, Deborah A.; Shiells, Clinton R.; Lowell, B. Lindsay (Journal of Labor Economics, 1995)
The Immigration Reform and Control Act of 1986 (IRCA) represents an attempt to use labor market regulation to control illegal migration into the United States by imposing fines on employers who hire unauthorized workers. Sanctions lower wages directly because they act as a tax on hiring additional workers. In addition, IRCA legalized many longtime illegal aliens. Legalization affects wages by changing the relative supply of authorized and unauthorized workers. This study estimates IRCA's impact on wages of manufacturing production workers in metropolitan areas and finds small but statistically significant effects: sanctions lower wages, while legalization raises them.